Pengukuran Niat Penggunaan Website Sebagai Sumber Informasi Mahasiswa Baru UNU Blitar Mengunakan Technology Acceptance Model - Pipit Ayuhana; Muhamat Maariful Huda; Rizqi Darma Rusydian Yusron (G-Tech: Jurnal Teknologi Terapan, 2024)
The use of information technology, especially web-based, is increasingly widespread and makes it easier for users to get the information they need. This website is also used as a source of information for new students, especially at UNU Blitar. There is information regarding registration, tuition fees, exam dates, announcements, and other information. So that this website can continue to develop, it is necessary to measure usage using a technology acceptance model which measures the intention to use a technology. Respondents in this research were new students at Nahdlatul Ulama University, Blitar, to measure variables that influence the use of websites as a source of information. As a tool for testing influential variables, partial least squares are used. The model built by researchers has an r-square value for the intention to use variable of 52% which answers the intention to use the website as a means of seeking information, however there are still 48% unknown variables that can strengthen the intention to use the website as a means of seeking information